Stress, Coping Strategies and Life Satisfaction of Guidance Practitioners in Private Secondary Schools in the Province of Cavite - Mendoza, Michael Alix; Quicho, Jervin Dinglasan; Costa, Liza C. (Future Science / FSH-PH Publications, 2025)
The main purpose of this study was to investigate the mediating role of coping strategies on the perceived stress and life satisfaction of Guidance Practitioners in Private Secondary Schools in the Province of Cavite. The study utilized descriptive-correlational design. The participants in this study were fifty three (53) guidance practitioners from private secondary schools in the province of Cavite that were determined through the use of purposive sampling technique. Majority of the participants were affiliated in non-sectarian private secondary schools. Most of them were guidance advocates and guidance associates. There were only few registered guidance counselors participated in the study. In addition, majority of them were 4-6 years in service as guidance practitioners. An online survey was conducted through google forms to the participants to measure the three main variables of the study: Perceived Stress Scale by Sheldon Cohen, Brief-COPE by Charles Carver, and Satisfaction with Life Scale by Ed Diener. The findings revealed that most of the participants have a moderate level of perceived stress. The participants were also obtained a high level of coping strategies. And, most of them are satisfied with their lives at present. The results also showed that there was moderate small negative relationship between perceived stress and life satisfaction level of the participants. However, there was no significant relationship between the perceived stress and coping strategies in terms of problem-focused coping and emotion-focused coping except to the avoidant coping that was significantly related to the perceived stress. Overall, the perceived stress and coping strategies were not significantly related. Also, the coping strategies and life satisfaction were not significantly related. Furthermore, the findings revealed that coping strategies did not serve as mediator on the relationship of perceived stress and life satisfaction. However, the perceived stress is negatively significant predictor of life satisfaction. With all of this, the study recommends that the Department of Education, Philippine Guidance and Counseling Association and future researchers utilize the findings of this study as a guide and to further enhance this study for the benefit of the guidance practitioners.